THE EFFECT OF MAULI BANANA (Musa acuminata) STEM EXTRACT GEL APPLICATION WITH 37.5% CONCENTRATION ON FIBROBLAST CELL COUNT (In Vivo Study On Wound Healing Process of Male Wistar Rat (Rattus norvegicus) Buccal Mucosa) - Rifasanto, Moh. Ihsan; Laillyza Apriasari, Maharani; Taufiqurrahman, Irham (Dentino, 2018)
Background: Wound healing is the body process to improve tissue intergrity caused by wound. Mauli banana stem is a potential plant which can be used as a medicine to accelerate wound healing. Mauli banana stem extract has some contents such as tannin and saponin which has immunomodulatory properties. Previous study states that mauli banana stem extract gel with 37,5% concentration can accelerate the healing of traumatic ulcers. Purpose: To analyze the effect of mauli banana stem extract gel application with 37,5% concentration on fibroblast cell count in wound healing process of oral mucosa wistar rat on the 7th day. Material and Methods: This study was a true experimental design with posttest only control group design. It consisted of three treatment groups: a group which given mauli banana (Musa acuminata) stem extract gel with 37,5% concentration, hydroxypropyl methylcellulose gel (negative group) and patent drug gel containing Aloe vera (positive group). Result: The mean value of fibroblast cell count in wound healing process on the 7th day of the treatment group (28,57), negative group (20,14), and positive group (23). One-way Anovaâs test had shown a significant difference. Post Hoc LSD test showed a significant difference between mauli banana stem extract gel with 37,5% concentration with hydroxypropyl methylcellulose gel and patent drug gel containing Aloe vera. Conclusion: The application of mauli banana stem extract gel with 37,5% concentration can increase fibroblast cell count on the 7th day in wound healing process of oral mucosa.